Design and Build The Game "Solid Shapes Explorer" Based on Android: Rancang Bangun Game "Solid Shapes Explorer" Berbasis Android - Kurniawan Putra, Ade; Primasetya Armin, Aidil (JOINCS (Journal of Informatics, Network, and Computer Science), 2024)
In mathematics lessons in elementary schools, the learning methods used by teachers are often still conventional, which can reduce students' interest in learning, especially at the elementary level, making them feel that math is not fun. The problem faced by the 5th grade teacher of UPT SD Negeri 192 Gresik is the difficulty of students in understanding the material of geometry, especially the formula for calculating the area and volume of various geometry. The limited learning media used, especially in the material of geometry, causes students to feel bored and have difficulty understanding the material. This research aims to design and produce an educational game. which can be used as a student learning tool related to geometry. In this research, using Game Development Life Cycle (GDLC) as the method used. The pretest and posttest results for the Solid Shapes Explorer game tested showed that the average pretest score of 20 students was 63.5, while for the posttest, the average student score reached 82. From the calculation results, it can be seen that the average posttest score shows an increase compared to the pretest score, with a difference of about 18.5 It can be stated that the use of learning through the Solid Shapes Explorer game has succeeded in improving students' understanding of geometry material.